Corrosion and tribocorrosion behavior of Ti−TiB−TiNx in-situ hybrid composite synthesized by reactive hot pressing. (October 2017) - Silva, J.I.; Alves, A.C.; Pinto, A.M.; Toptan, F.
Abstract: Ti and its alloys are attractive materials for variety of fields, including biomedical implants, however, the wear behavior is yet to be improved. In the present work, Ti−TiB−TiNx in-situ metal matrix composites were synthesized by reactive hot pressing using a Ti-BN powder blend. Corrosion behavior was investigated in 9 g/L NaCl solution at 37 °C by performing potentiodynamic polarization and electrochemical impedance spectroscopy. Tribocorrosion behavior was investigated using reciprocating tribometer, against an alumina ball, under 1 and 10 N normal load, 1 and 2 Hz frequency, in 9 g/L NaCl solution at 37 °C. Results suggested that TiB and TiNx in-situ phases did not deteriorate the corrosion behavior of Ti but significantly improved the tribocorrosion behavior under 1 N.